Short-Term Parental Migration and Intergenerational Educational Persistence - Sharma, Swati (Animo Repository, 2024)
This study examines the mechanisms through which short-term parental migration affects intergenerational educational persistence, using a sample of 40,922 Indian father-child pairs from the Indian Human Development Surveys. A flexible modeling approach was used that allows for heterogeneous effects of social origins and structural features of the Indian education system on different educational transitions of the child. Results show that parental migration increases intergenerational educational persistence. In particular, persistence increases for higher educational transitions when parental migration is motivated by economic distress or when the left-behind children are engaged in household responsibilities. Lack of parental supervision increases persistence across all educational transitions. Educational disruptions associated with child migration increase persistence for the non-literate to primary transition but not for the higher educational transitions. These results are robust to potential endogeneity concerns for a wide range of assumptions regarding the form of unobserved heterogeneity.